Kajian Sistematik: Strategi Pembelajaran Klinik di Setting Rawat Jalan - Ova Emilia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2015)
Background: Clinical education in outpatient settings acknowledged as a challange for clinical instructors, which they had to provide efficient and qualified service to the patients while also including educational components that significantly handful for clinical students. We recognized many learning strategies to encounter those challanges, but only few of them that had been evaluated. This systematic review were provided to compare various clinical learning strategies which are useful in outpatient setting.Method: Literature searching has done according PubMed database that related in topics such the impact of clinical education in outpatient setting on learning, outcome, and also efficiency of the outpatient clinics. There were no boundary setting that cone in this systematic review.Results: There were two learning strategy: “One Minute Perceptor” (OMP) and SNAPPS has been showed to be effective in increasing educational-learning process and service outcome. Another two strategies such as “Aunt Minnie” pattern recognition and “Active Demonstration” were also promising but hadn’t been sufficiently studied. There weren’t any of those strategies showed their impact in outpatient clinic setting efficiency.Conclusion: OMP and SNAPPS may be used for clinical mentoring in outpatient settings to increase learning process and learning outcome, while pattern recognition and activated demonstration hadn’t show any promising evidence.